Modeling and simulation of hairy root growth - Bastian, Peter; Engwer, Christian; Jäger, Willi; Ptashnyk, Mariya; Wetterauer, Bernhard (Mathematics – key technology for the future, 2008)
A multiscale approach is presented to model growth of hairy roots. On the macroscopic scale, a continuous model is derived, which includes growth and nutrient transport. Water transport is considered on the microscopic scale. A Discontinuous Galerkin scheme for complex geometries is used to compute the permeability of root bulks. This permeability constitutes the linkage between microand macroscopic scale. The models are applied then to describe shaker cultures of hairy roots and simulations are compared to measurements.